Dilema Peran Digitalisasi Sistem Akuntansi terhadap Kualitas Laporan Keuangan: Antara Peningkatan Akurasi dan Risiko Kesalahan Sistemik - Nurawalia Pratiwi; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The digitalization of accounting systems has transformed financial management and reporting processes through the adoption of integrated information technology. This study aims to analyze the dilemma of accounting system digitalization on the quality of financial reporting, particularly the balance between improving information accuracy and the risk of systemic errors. The study employs a qualitative approach using a library research method by critically analyzing scientific journals, academic books, financial reporting standards, and other relevant publications. The findings indicate that digitalization enhances efficiency, timeliness, consistency, and the accuracy of financial reporting through automation and data integration. On the other hand, the high level of system integration increases the potential for systemic errors caused by input inaccuracies, system configuration failures, technological disruptions, and weak internal controls. The quality of financial reporting is influenced by an organization's ability to integrate technology, strengthen users' digital competencies, and implement effective internal controls to minimize systemic risks while optimizing the benefits of digital transformation.